Phlegmasia Cerulea Dolens and May–Thurner Syndrome in the first trimester of Pregnancy - Ladha, Aliya B.; Fareeduddin, Rizwana (American Journal of Perinatology Reports, 2016)
Background Venous thromboembolism in pregnancy remains one of the leading causes of morbidity and mortality.Case A young, gravid patient presented with a cyanotic, edematous left lower extremity with no distal pulses palpable. She was emergently taken to the operating room and was found to have extensive iliofemoral thrombosis requiring femoral angioplasty and embolectomy with 43.7-rad intraoperative radiation exposure. Phlegmasia cerulea dolens and May–Thurner syndrome were diagnosed.Conclusion Timely diagnosis and prompt surgical management are necessary due to the limb-threatening nature of this condition. Despite maternal radiation exposure, the nature and extent of fetal effects depends upon radiation dose and gestational age.
Keywords: venous thromboembolism; May–Thurner syndrome; pregnancy; phlegmasia cerulea dolens